The Role Of Knowledge Management In Product Development Performance: A Review - Ng, Poh Kiat; Goh, Gerald Guan Gan; Eze, Uchenna Cyril (Journal of Knowledge Management Practice, 2011)
The advancement towards knowledge-driven competition based on innovation and product quality, have redefined the strategy space and competitive nature of many industries. However, researchers believe that although employee motivation in knowledge sharing is important, it is often neglected. Therefore, this paper aims to investigate the role of knowledge management in product development performance. In this study, findings from the literature review are used to develop a conceptual relation on how knowledge management influences product development performance. Based on the review of the extant literature, it was found that socialization and internalization play a more essential role in enhancing product development performance due to their more practical and convenient implementations in product development. Managers and engineers should work together to create more platforms that can harness socialization activities such as coffee klatches, technical sharing and team building activities. Apart from that, management should organize training programmes to internalize the explicit knowledge and actualize concepts about strategy, tactics, innovation or improvement.
Keywords: Knowledge management; Innovation; Product development